Свята пісні та фольклорні музичні колективи в Литві: вираження етнокультурної ідентичності - Забелене, А. (Народна творчість та етнологія, 2011)
The contribution of the Song Festivals and folklore groups to the preserving and strengthening of ethnical and cultural identity of the inland and outland Lithuanians is examined in the article. It has been accentuated that the common festivals of the choirs, folklore ensembles, dancers, folk masters ensure the continuity, cherish traditional culture and popularize it in the modern society. The directors and participants of the Lithuanian folklore ensembles reckon recreation and leisure, self-expression, execution of ethnical music, communication and prolongation of the ethnocultural traditions as the main motivations of their activities.